Fate ignoranti, Le - Buy, Margherita, 1962-; Accorsi, Stefano, 1971-; Yılmaz, Serra; Gabriel, Garko; Blanc, Erika, 1942-; Renzi, Andrea; Candemir, Koray; Valia, Lucrezia; Filippo, Nigro; Bacchi, Ivan.; Maurizio Romoli; Recano, Carmine; et al. (Italy, 2001)
AIDS doctor Antonia's husband is killed by a car. She gets depressed until she learns he had been cheating on her with a man. Following her newly born curiosity for life, she goes to see her husband's lover, Michele, and finds a huge apartment that he shares with gay and transgendered friends, including a Turkish immigrant and a prostitute. Antonia is reluctant to tell these people of her relationship to the dead man, but needs prompting to move on to a new phase of her life.
Keywords: Drama